2009
DOI: 10.1158/1078-0432.ccr-08-1968
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Pulmonary Carcinoma Following Head and Neck Cancer by Genetic Analysis

Abstract: Purpose: Patients with head and neck cancer often develop a lung tumor that can be diagnosed as distant metastasis (DM) or second primary tumor (SPT). In this study, we useTP53 mutation analysis for validation of an allelic loss marker panel and a decision algorithm for distinguishing between DM and SPT. Experimental Design: Tumor pairs of 39 patients were analyzed for TP53 mutations, for patterns of allelic loss and immunohistochemical analysis of p53 expression. Results of these three analyses were compared,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Although such techniques are time-consuming, they are becoming more and more suitable for routine application. [6][7][8] Reported five-year survival rates after resection of metachronous lung lesions range from 19 to 43 per cent; however, as in the current series, these percentages are still based on small patient cohorts (n ≤ 55). 4,5,[9][10][11] Winter et al found a significantly better survival, comparing operated and non-operated patients by matched pair analysis, in 67 patients with pulmonary metastases of head and neck cancer.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…Although such techniques are time-consuming, they are becoming more and more suitable for routine application. [6][7][8] Reported five-year survival rates after resection of metachronous lung lesions range from 19 to 43 per cent; however, as in the current series, these percentages are still based on small patient cohorts (n ≤ 55). 4,5,[9][10][11] Winter et al found a significantly better survival, comparing operated and non-operated patients by matched pair analysis, in 67 patients with pulmonary metastases of head and neck cancer.…”
mentioning
confidence: 55%
“…[6][7][8]32,33 However, these techniques are complex and sometimes time-consuming, and not universally available for pre-operative analysis of tumour tissue. Although one might have expected better survival rates after treatment for second primary lung cancer, compared with treatment for lung metastases, we were not able to demonstrate such a difference in a group of patients with molecularly defined lung SCC lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This distinction greatly influences patient prognosis and could guide treatment strategies, but the nature of the lung nodule is often difficult to discern using standard clinical and histologic parameters. Some have advocated comparative analysis of various genetic parameters such as gene mutations or microsatellite alterations;(14,15,23,36) but implementation has been constrained by cost, technical considerations, and the inherent instability of a tumor’s genetic profile over time. HPV analysis is an attractive alternative given that HPV is an established causative agent for a subset of HNSqCCs, the incidence of these HPV-related HNSqCCs is rising to the point that they now dominate the head and neck oncology landscape, and HPV tumor analysis is relatively straightforward using widely available in-situ and immunohistochemical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of multiple tumors for patterns of microsatellite alterations, specific gene mutations and other molecular genetic parameters has been advocated as a better way to clarify the fundamental distinction between a second lung carcinoma and a lung metastasis. (14,15,23,36) Widespread integration of these novel strategies into routine clinical practice, however, has not been forthcoming. Transfer into the clinical arena has been limited by cost, technical feasibility, and the inherent instability of the genetic profile of a tumor over time.…”
Section: Introductionmentioning
confidence: 99%